Primary Pancreatic Lymphoma in a Patient with Maturity Onset Diabetes of the Young type 3 - Valentina Bozzoli; Maria Chiara Tisi; Luigi Pianese; Stefano Tumini; Vittoria Rufini; Maria Lucia Calcagni; Dario Pitocco; Alberto Larghi; Luigi Maria Larocca; Giuseppina Massini; Luciana Teofili; Francesco D'Alò; et al. (Mediterranean Journal of Hematology and Infectious Diseases)
Primary pancreatic lymphoma (PPL) is an extremely rare disease which occurs in pancreas, accounts for less than 1% of extra-nodal malignant lymphomas and 0,5% of cases of pancreatic masses. We report the case of PPL in a 15 year-old boy suffering from Maturity onset Diabetes of the young type 3 (MODY3) diagnosed at the age of 1 year